Approximation of sine-shaped functions by constants in the spaces L_p, p < 1 - Babenko, V. F.; Kofanov, V. A.; Pichugov, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate the best approximations of sine-shaped functions by constants in the spaces L_p for p < 1. In particular, we find the best approximation of perfect Euler splines by constants in the spaces Lp for certain p∈(0,1).